Nekaj premislekov o laboratorijskih preiskavah obnašanja zidov in zidanih konstrukcij pri potresni obtežbi - Tomaževič, Miha (Gradbeni vestnik, 2016)
Some aspects of testing and experimental research of seismic behaviour of masonry walls and buildings, based on the experience obtained at Slovenian National Building and Civil Engineering Institute, are discussed. Typical testing methods are presented and the influence of governing parameters, such as boundary conditions, loading protocols and scale effects, on failure mechanisms and test results, are analyzed. The conditions to be fulfilled when testing models of masonry buildings on shaking tables, are discussed. Finally, typical examples of experimental research to investigate various issues of seismic behaviour of masonry buildings are also briefly described.
Keywords: boundary conditions; case studies; loading protocols; modelne preiskave na potresni mizi; potek obremenitev; preiskave zidov; primeri; robni pogoji; shaking table model tests; testing of walls